Provável extrusão de núcleo pulposo aguda e não compressiva em um cão: Relato de caso - Franco, G. G. [UNESP]; Siqueira, E. G M D [UNESP]; Souza, J. A L D [UNESP]; Prado, L. O D C [UNESP]; Brandão, C. V S [UNESP]; Rahal, S. C. [UNESP]; Mamprim, M. J. [UNESP]; Quitzan, J. G. [UNESP]; Minto, B. W. [UNESP] (FapUNIFESP (SciELO), 2016)
Acute and non-compressive disc extrusion is characterized by the acute character of extrusion of the nucleus pulposus without real compression of the spine. It has been called low-volume and high speed disc herniation or disc explosions, and usually is associated with an intense exercise or traumatic episode. This report aims to present a case of an acute extrusion of nucleus pulposus with no compression of the spinal cord. A 3.5 year-old male dog of the Maltes breed, weighing 4.1kg was presented at the Veterinary Hospital with locomotion disorders and pain during manipulation with no history of trauma. At the physical and neurological examination, non-ambulatory paraparesis of acute onset with absence of proprioception and superficial pain in hind limbs was found, as well as pain on palpation of epaxial thoracolumbar spine. Magnetic resonance imaging (MRI) showed extensive hyper intense area in the thoracolumbar spinal cord, with no signs of spinal cord compression, and decreased intensity of the nucleus pulposus of the L1-L2 intervertebral disc. Additionally, a spinal cord edema in all thoracolumbar segments was seen that is characteristic of an acute extrusion of non-compressive nucleus pulposus. A presumptive diagnosis of non-compressive myelopathy was assumed. The dog was prescribed steroidal anti-inflammatory, analgesic, absolute rest and rehabilitation protocol, including acupuncture and physiotherapy. The patient recovered superficial pain in the pelvic limbs and evolved into ambulatory paraparesis after seven days. The results of this report suggested that MRI can be useful for making a presumptive diagnosis in dogs with a history of compatible clinical signs. Moreover, the conservative treatment in non-compressive disc extrusions can be feasible.
Probable acute non-compressive nucleus pulposus extrusion in a dog: Case report
Keywords: Extrusion; Intervertebral disc disease; Nucleus pulposus; Spinal cord injury